Semantic keyword-based search on structured data sources : first COST Action IC1302 International KEYSTONE Conference, IKC 2015, Coimbra, Portugal, September 8-9, 2015. Revised selected papers /: first COST Action IC1302 International KEYSTONE Conference, IKC 2015, Coimbra, Portugal, September 8-9, 2015. Revised selected papers. (2015) - Unknown
No abstract available